A persistent, TTX-sensitive sodium current in an invertebrate neuron with neurosecretory ultrastructure - Davis, RE (J Neurosci, 1988)
In the CNS of the giant barnacle (Balanus nubilus) a single pair of large neuronal somata (cross-commissural, or CC, cells), located near the entry of the median ocellar nerve, occasionally displays a prominent whitish luster. These somata have ultrastructure typical of neurosecretory cells: numerous Golgi complexes and abundant, large dense-cored vesicles (DCVs; size range, 75–275 nm). Injection of a CC cell with cobalt tracer shows that it arborizes over a 7 mm length of the contralateral peripheral nerve out of which it projects. The processes of the arbor are profuse and varicose; the varicosities are packed with DCVs similar to those in the soma. Stimulation of a single CC cell causes a substantial decrease in the number of DCVs and increases the incidence of clusters of small electron-lucent vesicles, as well as the occurrence of large electron-lucent vesicles and membrane-bound cisternae. We studied ionic currents flowing across this cell's somatic membrane with a single-electrode voltage clamp. Unusual among these currents is an inward current that is blocked by TTX but is essentially noninactivating. In current clamp, this “persistent” current causes the action potential to be prolonged (seconds) if opposing outward current is blocked with 4-aminopyridine. The inward current is carried by Na. Its amplitude depends on the external Na concentration, it is blockable by TTX, and it persists when the cell is bathed in Ca-free saline and/or Co. Other currents present in this cell include an outward current similar to molluscan A-current and a Ca current that contributes to the action potential (Stockbridge and Ross, 1986). The persistent Na current is partially activated at the cell's resting potential and, thus, may participate in determining the frequency of its impulse activity.